Chet tillarini o‘spirin yoshdagi o‘quvchilarga o‘rgatishda psix- ologik yondashuvlarning ahamiyati (SCIENCE and SOCIETY, 2022)
The given article discusses the psychological nature of teenagers, their psychological changes, English language teach- ing techniques, and the role of psychological approaches in teens foreign language learning.